2008
DOI: 10.1007/s12012-008-9021-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of Copper and Homocysteine in Pressure Overload Heart Failure

Abstract: Elevated levels of homocysteine (Hcy) (known as hyperhomocysteinemia HHcy) are involved in dilated cardiomyopathy. Hcy chelates copper and impairs copper-dependent enzymes. Copper deficiency has been linked to cardiovascular disease. We tested the hypothesis that copper supplement regresses left ventricular hypertrophy (LVH), fibrosis and endothelial dysfunction in pressure overload DCM mice hearts. The mice were grouped as sham, sham + Cu, aortic constriction (AC), and AC + Cu. Aortic constriction was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…The involvement of COX and SOD cuproenzyme activities in cardiac hypertrophy strengthens the idea of a positive impact of copper on angiogenic-related cardiac diseases. However, even if copper supplementation can rescue the cardiac dysfunction due to prolonged pressure overload and improve the electrical conduction [27,291], it must be observed that copper may enhance the detrimental effects of elevated homocysteinemia, a risk factor for cardiovascular pathologies, on cardiac endothelial function [292]. …”
Section: Copper and Angiogenic Diseasesmentioning
confidence: 99%
“…The involvement of COX and SOD cuproenzyme activities in cardiac hypertrophy strengthens the idea of a positive impact of copper on angiogenic-related cardiac diseases. However, even if copper supplementation can rescue the cardiac dysfunction due to prolonged pressure overload and improve the electrical conduction [27,291], it must be observed that copper may enhance the detrimental effects of elevated homocysteinemia, a risk factor for cardiovascular pathologies, on cardiac endothelial function [292]. …”
Section: Copper and Angiogenic Diseasesmentioning
confidence: 99%
“…On the other hand, dietary Cu restriction has been shown to induce myocardial TGF-␤ overexpression and fibrosis in rats (12). Finally, mice with pressure overload secondary to aortic constriction and chronic HF exhibit myocardial fibrosis and increased LOX activity that are prevented in animals treated with a Cu supplement (27). Therefore, although contradictory data have been reported, the available evidence points to the possibility that myocardial LOX overactivity may contribute to Cu deficiency-induced cardiac disease.…”
Section: Role Of Lox In Myocardial Fibrosismentioning
confidence: 99%
“…1, Cu may be excreted from cardiomyocytes together with other molecules in the form of Cu complexes. Under pressure overload condition, homocysteine (Hcy) levels increase in the heart (Hughes et al, 2008;Kang, 2011). Experimental and clinical studies over the last decade have demonstrated that high levels of Hcy associated with cardiovascular events (Malinow et al, 1999;Mansoor et al, 2000;Garnier et al, 2003) are accompanied by increased Cu concentrations in the blood (Mansoor et al, 2000;Jeremy et al, 2002;Shukla et al, 2007).…”
Section: Possible Mechanisms For Cu Efflux From the Heartmentioning
confidence: 99%
“…Altered collagen cross-links and an abnormal connective tissue ultrastructure were associated with an increase in cardiac lysyl oxidase (LOX) activity in the ascending aortic constriction mice, and Cu supplement returned the LOX activity to the baseline value (Hughes et al, 2008). Additionally, experimental evidence showed that the deletion of LOX-1 reduces cardiac hypertrophy and collagen accumulation following chronic ischemia in mice (Hu et al, 2007;Lu et al, 2012).…”
Section: Mechanisms For Cu-induced Reversal Of Pathological Cardiac Hmentioning
confidence: 99%